Prices and consumer purchasing preferences at the border: Evidence from a multi-country household scanner data set - Günter W. Beck; Hans-Helmut Kotz; Natalia Zabelina (Goethe University Frankfurt, Center for Financial Studies (CFS), 2016)
Studies employing micro price data to examine the extent of international goods market integration tend to find that borders induce arbitrage-impeding transaction costs which contribute to segment national markets. Analyzing household scanner price data from the three euro area countries Belgium, Germany and Netherlands, we document that Belgian households living in the vicinity of the border to Netherlands pay almost 10% more for the same good as their Dutch counterparts. German consumers on the other hand face prices that are on average up to around 3% smaller than those in the neighboring Netherlands. Counterfactual evidence for within-country price discontinuities provides no evidence of any existing border effects. The induced costs of crossing national borders amount to at least 13%. We also find evidence on border discontinuities in various household preference characteristics (such as demand elasticities and goods valuation) and household shopping patterns such as shopping frequencies.
urn:nbn:de:hebis:30:3-415839
Keywords: D12; D40; F40; 330; goods market integration; international price setting; border effects; price discrimination; demand elasticities; habit formation; scanner price data